Kinerja dan Motivasi Penyuluh Pertanian di Provinsi Jawa Barat - Nani Sufiani Suhanda; Amri Jahi; Basita G Sugihen; Djoko Susanto (Jurnal Penyuluhan, 2009)
A research to investigate the relationship of the agricultural extension agent (AEA) motivator-hygiene factors and their job performances at different agriculture extension institution in west java was conducted in August through Desember 2007.  The objectives of this study were:1) to identify their job performance and 2) to determine the relationship of the agent motivator-hygiene factors and their job performances in west Java Province.  A total of 260 AEA from 17 districts in West Java were selected by a stratified randomized sampling technique with proportional allocation as a sample of the study. Descriptive statistics were used to determine the agents’ description  on their motivator-hygiene factors,  whereas the Kendall coefficient of concordance W  was used to analyze  the relationship of AEA performance and their motivator-hygiene factors. The results shown that some substantial works need to be done in order to improve the agents’ performances due to low hygiene factors and insufficient of motivating factors.  Furthermore, the Kendall coefficient of concordance W obtained mostly high and highly significant. It could be concluded that AEA performed best in respectively involving informal leaders, farmer group development, extension work plan, using extension method, program planning; and performed well in evaluation and reporting subject matters development, farmer self reliance development, office maintenance and administrative, rural economic development and need assessment.  Finally, Agriculture extension agent performed unsatisfactorily in evaluation and reporting, networking and professional development.